Leveraging visual media to improve articulation skills in children with hearing impairments - Maspupah, Epah; Yunitasari, Septiyani Endang; Priyanti, Nita (Universitas Islam Negeri Raden Intan Lampung, 2024)
Background: Early childhood is a critical period for language and communication development. Deaf children often face significant challenges in acquiring articulation skills due to hearing impairments, which impact their ability to communicate effectively. Despite various interventions, there remains a need for effective, evidence-based strategies to support these skills.Aim: This study aims to evaluate the effectiveness of picture media in improving articulation skills in children with hearing impairments. By focusing on articulation rather than broader language skills, this research addresses a gap in existing literature.Method: A qualitative approach was employed, involving observations, interviews, and documentation to collect data over six months. The study analyzed changes in articulation skills in a deaf child before and after interventions using picture media. Instruments included standardized articulation tests and feedback from parents and teachers.Result: Findings reveal that picture media significantly enhance articulation skills, enabling children to associate sounds with visual cues effectively. Specific improvements were observed in the pronunciation of vowels and consonants, with gradual progress in constructing syllables and words. Unlike prior studies that primarily explore vocabulary development or general communication in deaf children, this research uniquely focuses on the direct impact of picture media on articulation skills. The study offers evidence-based insights for developing targeted educational interventions for children with hearing impairments.Conclusion: This study confirms the importance of using visual media, especially pictures, in the learning of children with hearing loss. This approach is not only effective in improving articulation skills but also supports children's optimal communication potential. Thus, picture media can be an important tool in inclusive education for deaf children.